2010
DOI: 10.1038/onc.2010.105
|View full text |Cite
|
Sign up to set email alerts
|

RSK2 is a kinetochore-associated protein that participates in the spindle assembly checkpoint

Abstract: The spindle assembly checkpoint (SAC) prevents anaphase onset until all the chromosomes have successfully attached to the spindle microtubules. The MAP kinase (MAPK) is an important player in this pathway, however its exact role is not fully understood. One major target of MAPK is the p90 ribosomal protein S6 kinase (RSKs) family. In this study, we analyse whether Rsk2 could participate in the activation of the SAC. Our data indicate that this protein is localized at the kinetochores under checkpoint condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The NTD of RSK2 transduces its substrates to accept the RSK2 activation signal [29]. Mad1 is a member of the Myc/Max/Mad family and a substrate of p90 ribosomal kinase and p70S6 kinase [30][31][32]. We showed that myricetin inhibits HGC-27 and SGC7901 cell proliferation through Mad1 and RSK2.…”
Section: Discussionmentioning
confidence: 94%
“…The NTD of RSK2 transduces its substrates to accept the RSK2 activation signal [29]. Mad1 is a member of the Myc/Max/Mad family and a substrate of p90 ribosomal kinase and p70S6 kinase [30][31][32]. We showed that myricetin inhibits HGC-27 and SGC7901 cell proliferation through Mad1 and RSK2.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, as RSK2 phosphorylated TIN2, and inhibiting this kinase in mitotic cells reduced TIN2 phosphorylation, TIN2 phosphorylation may be linked with functions of RSK2. In this regard, RSK2 promotes G2/M transition [35] and maintains spindle assembly checkpoint [36]. In summary, we demonstrate that first, only the two sites S295 and S330 in TIN2 are found to be phosphorylated, second, these two sites are preferentially phosphorylated at mitosis and third, RSK2 can phosphorylate TIN2 on these two residues.…”
Section: Discussionmentioning
confidence: 57%
“…7), the latter of which has similar indications in lower organisms (72). Whether low MSK2 expression is a cause or consequence of aneuploidy is unknown, but based on previous findings of a prolonged G1 phase in MSK2-deficient cells (44) and that a closely related family member is a kinetochore-associated protein that participates in the spindle assembly checkpoint (73), it is likely that reduced MSK2 expression prevents the localization and function of several proteins involved in cell cycle progression. Thus, further investigation is required to determine whether MSK2 prevents aneuploidy generation directly or indirectly via DNMT1 , AURKA / AURKB and/or other cell cycle associated genes and the exact mechanism by which MSK2 mediates its function.…”
Section: Discussionmentioning
confidence: 99%